The Structure of Middle Maithili - Yadav, Ramawatar (Nepalese Linguistics, 2022)
(As Gleaned from the Hand–Copied Newari Manuscripts of Maithili Plays and Songs Composed by Malla Rulers of the Medieval Nepālamaṇḍala and Archived in the Nepāla Rāṣṭrīya Abhilekhālaya in Kathmandu) The keynote speech discusses Newari's orthographic peculiarities that deftly represent the Middle Maithili sound system, and describes the linguistic structure of Middle Maithili as enshrined in the numerous manuscripts published, to date, in Nepal, India, Germany, and Japan. The presentation is a culmination of my earnest endeavors to incessantly and assiduously seek to retrieve and create and assimilate and disseminate indigenous knowledge coded in the precious Newari manuscripts of the Maithili language archived in the National Archives of Nepal.